A Multiple-Starting-Path Approach to the Resource-Constrained kth Elementary Shortest Path Problem. (22nd March 2015) - Tae, Hyunchul; Kim, Byung-In
Abstract : The resource-constrained elementary shortest path problem (RCESPP) aims to determine the shortest elementary path from the origin to the sink that satisfies the resource constraints. The resource-constrained k th elementary shortest path problem (RCKESPP) is a generalization of the RCESPP that aims to determine the k th shortest path when a set of k - 1 shortest paths is given. To the best of our knowledge, the RCKESPP has been solved most efficiently by using Lawler's algorithm. This paper proposes a new approach named multiple-starting-path (MSP) to the RCKESPP. The computational results indicate that the MSP approach outperforms Lawler's algorithm.